2015
DOI: 10.1136/bmjopen-2015-009449
|View full text |Cite
|
Sign up to set email alerts
|

Postdischarge mortality in children with acute infectious diseases: derivation of postdischarge mortality prediction models

Abstract: ObjectivesTo derive a model of paediatric postdischarge mortality following acute infectious illness.DesignProspective cohort study.Setting2 hospitals in South-western Uganda.Participants1307 children of 6 months to 5 years of age were admitted with a proven or suspected infection. 1242 children were discharged alive and followed up 6 months following discharge. The 6-month follow-up rate was 98.3%.InterventionsNone.Primary and secondary outcome measuresThe primary outcome was postdischarge mortality within 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 22 publications
2
88
1
Order By: Relevance
“…The methods have been previously described in detail. 6 Briefly, this was a two-site, hospital-based cohort study in Mbarara, Uganda. All children between 6 months and 5 years of age who were admitted to either site with a suspected or proven infection were screened for eligibility.…”
Section: Methodsmentioning
confidence: 99%
“…The methods have been previously described in detail. 6 Briefly, this was a two-site, hospital-based cohort study in Mbarara, Uganda. All children between 6 months and 5 years of age who were admitted to either site with a suspected or proven infection were screened for eligibility.…”
Section: Methodsmentioning
confidence: 99%
“…This is likely to be because children with severe signs more often died during the inpatient phase. However, in Uganda, in a study where severe pneumonia was not strictly defined according to WHO criteria, two features of severity, oxygen saturation and coma score were associated with post‐discharge mortality after adjustment for HIV and nutritional status …”
Section: Commentmentioning
confidence: 99%
“…[11][12][13] Two of these studies included hospitalised children with a diagnosis of pneumonia, but not necessarily severe pneumonia according to World Health Organization (WHO) guidelines, from The Gambia (n = 2725) 11 and Uganda (n = 389). 12 Only the Ugandan study 12 examined the effect of HIV status. One other study, from Bangladesh (n = 369) 13 used WHO diagnostic criteria for severe pneumonia, but only included HIV-uninfected children with Severe Acute Malnutrition (SAM).…”
mentioning
confidence: 99%
“…Current guidelines recommend that children admitted with cSAM are discharged and transferred to community care when their medical complications, including oedema, are resolving, they are clinically well and alert, and have good appetite, rather than hospital discharge being based on anthropometric criteria (WHO, 2019). However, children with cSAM experience a high rate of mortality and readmission in the months following hospital discharge especially in sub-Saharan Africa (Berkley et al, 2016;Chhibber et al, 2015;Dubray et al, 2008;Kerac et al, 2009;Moisi et al, 2011;Ngari et al, 2017;Trehan et al, 2013;Veirum, Sodeman, Biai, Hedegård, & Aaby, 2007;Wiens et al, 2013;Wiens et al, 2015). Recent systematic reviews reported paediatric post-discharge mortality rates in resource-poor countries of up to 18% that may exceed in-hospital mortality rates in many settings (Nemetchek et al, 2018;Wiens et al, 2013).…”
Section: Introductionmentioning
confidence: 99%